Genetic divergence in ground nut (Arachis hypogaea L.) - Satyenrda Singh Raghuwanshi; V. H. Kachhadia; J. H. Vachhani; L. L. Jivani and; M. B. Patel (Electronic Journal of Plant Breeding, 2016)
Divergence analysis among fifty groundnut genotypes using Mahalanobis’s D2 statistic grouped into twenty-seven clusters. The maximum inter-cluster distance was found between clusters XXVII and XVIII (D=22.53) followed by clusters XXVI and XVIII (D=20.79) and XXVII and XXIII (D=20.63) indicated that these groups of genotypes were highly divergent from each other. The genotypes in above clusters revealed substantial difference in the means for important yield contributing characters suggesting that the genotypes belonging to these clusters form ideal parents for improvement in groundnut.